99mTc labelled complexes with secnidazole xanthate: Synthesis and evaluation as potential radiotracers to target tumor hypoxia. (October 2018) - Lin, Xiao; Ruan, Qing; Zhang, Xuran; Duan, Xiaojiang; Teng, Yanguo; Zhang, Junbo
Abstract: In this study, the commercially available secnidazole was successfully converted to secnidazole xanthate (SNXT), in which the xanthate group can act as a bifunctional chelator to coordinate with 99m Tc. 99m Tc-nitrido complex of SNXT( 99m TcN-SNXT) and 99m Tc-oxo complex of SNXT( 99m TcO-SNXT) were prepared with high radiochemical purity. Both of the complexes were found to be stable in vitro and to exhibit similar hydrophilicity. In addition, comparative in vitro cell uptake studies under anoxic and normoxic conditions demonstrated that both agents were preferentially taken up by hypoxic cells. Biodistribution studies in mice bearing S180 tumor showed 99m TcO-SNXT exhibited a higher tumor uptake and tumor-to-muscle ratio than 99m TcN-SNXT. Furthermore, in SPECT imaging study, 99m TcO-SNXT exhibited a clear accumulation in tumor at 2 h post-injection, suggesting its potential to be a novel hypoxia imaging agent. Highlights: 99m TcN-SNXT and 99m TcO-SNXT complexes showed hypoxic selectivity, similar hydrophilicity and good in vitro stability. Biodistribution studies in mice bearing S180 tumor showed both complexes could accumulate in tumor and 99m TcO-SNXT exhibited higher tumor uptake and tumor-to-muscle ratio than 99m TcN-SNXT. Single photon emission computed tomography (SPECT) imaging studies indicated 99m TcO-SNXT was able to accumulate in tumor.